O impacto dos precedentes como instrumento de efetividade da proteção social previdenciária na tutela dos direitos do segurado do Regime Geral de Previdência Social - Simonato, Geisla Luara (2022)
This dissertation addresses the evolution of the concept of access to justice and the intensification of judicialization in matters of fundamental rights, especially since the promulgation of the 1988 Constitution, which legally refounded the country, transforming it into a Democratic State of Law. It demonstrates that access to a fair legal order is being impacted by the increase in litigiousness, notably in relation to rights that are not satisfied by the public powers, but that have legal regulation and, within this intense judicialization, the INSS participates as a contumacious litigant and with massive participation in the total number of lawsuits in the judiciary. Due to the intense judicialization, repeated lawsuits are formed, which have as an uncommon point to demonstrate the non-observance of a certain social security rule. In this paper, we intend to demonstrate how the system of precedents rationalizes the provision of jurisdiction; impacts the protection of the rights of the insured, in the scope of administrative and jurisdictional protection and provides the containment of judicialization in social security matters